Problems of Design and Construction of Buildings and Structures in Seismic Areas, on Weak Moistened Clay and Subsidence Loess Bases (International Journal of Scientific Trends, 2024)
This article presents the features of the design and construction of buildings and structures on weak clay and subsident loess soils in seismic areas. A recommendation is given on vibration compaction of weak moistened clay and subsident loess soils of the foundations of buildings and structures, as well as bulk soils filled up around the foundation in seismically active areas.